Pseudocoloring method for 3-D contouring - Rabal, Héctor J. (1982)
The interference properties of white light speckle pattern obtained with an optical system not corrected for chromatic aberration are applied to pseudocolor encode the depth level contours of a 3-D diffusing object. At a first step, a recording of the different encoded images of depth levels is done. In a second step, a reconstructed pseudocolored image is obtained, where different color assignements can be tuned by changing the position of a spatial filter slit. Also, a quantitative contouring can be made scanning the pseudocolored image plane with a spectroscopic device.